Do Indonesian medical practitioners approve the availability of emergency contraception over-the-counter? A survey of general practitioners and obstetricians in Jakarta - Syahlul Dyna E; Amir Lisa H (BMC, 2005)
Abstract Background Few studies have examined the attitude of medical practitioners towards the availability of emergency contraception (EC) without prescription. In Indonesia, EC (either Yuzpe regimen or Postinor-2) is available by prescription only. We aimed to examine the level of knowledge, attitudes and practices of medical practitioners in Indonesia about EC, in particular their attitudes to the availability of EC over-the-counter (OTC), using a questionnaire. Methods Data were collected by an anonymous structured questionnaire. Questionnaires were distributed to general practitioners in 36 Community Health Centres and 25 private clinics using stratified random sampling according to area in Jakarta, and to obstetricians practicising in 24 government and private hospitals and eight private clinics in Jakarta. Two hundred and five general practitioners and 142 obstetricians and gynaecologists participated; overall response rate was 75%. Results Although most participants were familiar with EC, only 22% received a very good knowledge score (4 or 5/5 answers correct), while 52% received a poor score (0-2/5 correct). Most participants did not support the OTC availability of EC (70%). Logistic regression identified that participants who prescribed EC had an Odds of 3.8 (95% CI 1.90, 7.73) of approving OTC EC, after adjustment for age and speciality. Conclusion Although many organisations are working towards OTC availability of EC, it needs to be recognized and addressed that doctors who do not prescribe EC are unlikely to support the increased availability of EC.